Sugarcane growth and nutrition levels are differentially affected by the application of PGPR and cane waste. Issue 6 (13th April 2018) - Santos, Roberta M.; Kandasamy, Saveetha; Rigobelo, Everlon Cid
Abstract: Mineral and organic fertilization can be optimized by using rhizobacteria which increases dry matter, yield, and nutrients in the soil and plant, among the other biological inputs. However, the discovery of single microbes or a consortium that can benefit plants has been a challenge. In this context, this study aimed to evaluate the effects of Bacillus subtilis and Bacillus pumilus combined with mineral fertilization and sugar and alcohol industry by‐products in presprouted and the initial growth phase of sugar cane seedlings. The study was carried out in two phases. Phase 1 included presprouted seedlings with T1 = untreated control, T2 = B. subtilis, T3 = B. pumilus, and T4 = B. subtilis + B. pumilus treatments. Phase 2 included the same treatments with four types of fertilization: F1 = mineral fertilization, F2 = mineral fertilization + vinasse, F3 = mineral fertilization + filter cake, and F4 = mineral fertilization + filter cake compost. Of the phase 1 treatments, T2 ( B. subtilis) was the best promoter of root growth and the total dry matter compared to the control with an increase of 23.0% compared to the control. In phase 2, B. pumilus application, increased the total dry matter by 13%, the number of tillers by 37%, and the diameter of the tillers by 48% when combined with mineral fertilization. The combined application of B. subtilis and B. pumilus increased the phosphorus content by 13% in soil treated with mineral fertilization and filter cake compost. The results of the this study strongly suggest that the use of B. subtilis and B. pumilus together with these by‐products can improve soil fertility parameters and decrease adverse effects associated with vinasse fertilization, in addition to providing shoot and root growth and providing collective synergy for a high yield of sugarcane production with environmental benefits. Abstract : The use of Bacillus subtilis and Bacillus pumilus as bioinoculant has been shown as a good alternative to plant growth promoting in sugar cane production in different kind of fertilizations using by‐product from sugar cane industry.